English Loanwords in the Destinasi Indonesia Magazine (Kata Serapan Bahasa Inggris dalam Majalah Destinasi Indonesia) - Apriana Nugraeni; Teguh Setiawan (Indonesian Language Education and Literature, 2021)
This research to describe English loanwords in the Destinasi Indonesia printed magazine, which focuses on travel, tourism destination guidance, and culinary. It focuses on several types, strategies, and equivalences of form, pronunciation, and meaning of those languages. The research used qualitative content analysis on a written document. The results show that types of English loanwords in Indonesian are in the form of words and phrases. The strategies are adoption, adaptation, translation, and creation. In the adoption strategy, the researchers invented partial and full adoption. They also discovered terms with the same form and meaning but distinct pronunciation in equivalences of form, pronunciation, and meaning. The pronunciation and meaning are the same, but the form is different. The concept is the same, but the form and pronunciation are different, or the points are the same as a whole. These English loanwords have profoundly modernized Indonesian lexicons.Penelitian ini bertujuan untuk mendeskripsikan kata serapan Bahasa Inggris dalam majalah Destinasi Indonesia yang membahas perjalanan, panduan destinasi wisata, dan kuliner. Penelitian berfokus pada tipe unsur serapan, strategi, serta kesejajaran bentuk, lafal, dan makna antara kedua bahasa. Penelitian menggunakan pendekatan kualitatif analisis isi pada dokumen tertulis. Hasil penelitian menunjukkan tipe unsur serapan Bahasa Inggris dalam Bahasa Indonesia adalah kata dan frasa. Strateginya adalah adopsi, adaptasi, terjemahan, dan kreasi. Dalam strategi adopsi, ditemukan adopsi sebagian dan penuh. Pada kesejajaran bentuk, lafal, dan makna, ditemukan kata yang memiliki bentuk dan makna sejajar, lafal berbeda. Lafal dan makna sejajar, bentuk berbeda. Makna sejajar, bentuk dan lafal berbeda atau sejajar secara keseluruhan. Kata serapan Bahasa Inggris memodernisasi leksikon dalam Bahasa Indonesia.